[3-[(1-Methylpiperidin-4-yl) methyl] arylsulfonyl]-1H-indoles: Synthesis, SAR and biological evaluation as a novel class of 5-HT6 Receptor Antagonists - NIROGI, RAMAKRISHNA V S; BADANGE, RAJESH KUMAR; KANDUKURI, KIRAN KUMAR; KHAGGA, MUKKANTI (Journal of chemical sciences (Bangalore, India), 2015)
In continuation to our efforts to develop better treatment options for cognitive decline, we have been focussing on 5-HT 6 receptor (5-HT 6 R) antagonists, which are known to be involved in improving cognitive function in numerous animal models. In this paper, we report a novel series of [3-[(1-Methylpiperidin-4-yl) methyl] arylsulfonyl]-1 H -indole derivatives as potent and selective 5-HT 6 R antagonists. The lead compound from this series shows potent in vitro binding affinity, functional antagonistic activity at 5-HT 6 R, good pharmacokinetic profile, excellent selectivity and no Cytochrome P450 liabilities. Graphical Abstract We report a novel series of [3-[(1-Methylpiperidin-4-yl) methyl] arylsulfonyl]-1 H -indole derivatives as potent and selective 5-HT 6 R antagonists. The lead compound from this series shows potent in vitro binding affinity, functional antagonistic activity at 5-HT 6 R, good pharmacokinetic profile, excellent selectivity and no CYP liabilities.